Ciri Khas Permainan Tradisional Lompat Kodok di Kota Bengkulu - Ela Pebriani; Henni Mayasari; Nurhasanah Bilqisth; Dela Emilia; Pauziah Lipita Sari; Dwinda Meisa; Neli Pebriyanti (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the characteristics of the traditional game of engklek and its relevance in supporting early childhood development in Bengkulu City. Traditional games, as part of local wisdom, play an important role in stimulating children’s cognitive, social, emotional, and motor development. This study employs a qualitative approach with data collection techniques including observation, interviews, and documentation. The research subjects consisted of early childhood education teachers and children aged 5–6 years at several early childhood education institutions in Bengkulu City. Research findings indicate that the game of hopscotch is characterized by the use of simple materials, motor activities that involve physical balance, and a high degree of social interaction. In addition, the game also instills educational values such as discipline, honesty, and cooperation. Hopscotch has proven to be a relevant learning tool capable of supporting children’s holistic development.